IMPACT OF LEVERAGE AND FINANCIAL DISTRESS ON ACCOUNTING CONSERVATISM - Meilinda; Santi Susanti; Sri Zulaihati (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the effect of financial distress and leverage on accounting conservatism. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020, totaling 165 companies. The sampling technique used was purposive sampling so that the number of samples in this study was 52 companies. Sources of data used are secondary data obtained from financial statements. The research method uses quantitative methods. The data analysis technique used consisted of descriptive statistical analysis, multiple linear regression analysis, analysis requirements test, classic assumption test, and hypothesis testing with SPSS version 26 software. The results of this study resulted in the following facts: (1) Financial distress partially has no significant effect on accounting conservatism. (2) Leverage partially has no significant effect on accounting conservatism. (3) Financial distress and leverage simultaneously have no significant effect on accounting conservatism.